Characterization of the complete chloroplast genome of styrax macrocarpus (Styracaceae), an endemic species from China - Tingting Tong; Lili Shao (Mitochondrial DNA. Part B. Resources, 2020)
The whole chloroplast genome of Styrax macrocarpus, an endemic species distributed in China, is determined in this study. The whole chloroplast genome size is 157,805 bp in length, containing a large single-copy region (LSC, 87,628 bp) and a small single-copy region (SSC, 18,267 bp), which were separated by a pair of inverted repeats (IRs, 25,955 bp). One hundred thirty one genes were detected from this genome, including 85 protein-coding genes, 38 transfer RNA genes, and 8 ribosomal RNA genes. The phylogenetic analysis suggested that the S. macrocarpus is closely clustered with S. japonicus with strong support values.